Allogenic Endothelial Cells Differentially Modulate the Expansion of Anti-Inflammatory FoxP3 High Regulatory T Lymphocytes According to Their State of Activation. (July 2018) - Cross, Amy; Lion, Julien; Poussin, Karine; Glotz, Denis; Mooney, Nuala
Abstract : Endothelial cell activation and microvascular inflammation are hallmarks of antibody-mediated rejection. This activation is evidenced by the reduplication of the capillary basement membrane, endothelial swelling and changes in intragraft endothelial-associated transcripts. During antibody-mediated rejection, donor specific antibodies targeting HLA class II antigens are prevalent and deleterious. The healthy microvascular endothelium readily expresses HLA-DR, yet both HLA-DR and HLA-DQ are significantly upregulated during allograft rejection; this may be associated with endothelial activation. The changing expression of HLA class II by the endothelium may contribute to allorecognition, the generation of de novo DSA and DSA-mediated damage. In an in vitro model of pro-inflammatory activation of microvascular endothelial cells, a relatively short exposure to interferon gamma (IFNγ) was sufficient to produce HLA-DR+ HLA-DQ- activated endothelial cells (aEC), whilst a longer and more intense regimen using IFNγ and tumor necrosis factor alpha (TNFα) was required to produce HLA-DR++ HLA-DQ+ chronically activated endothelial cells (caEC). Additionally, the pro-inflammatory conditions induced concomitant changes in the expression of key costimulatory, adhesion and complement-inhibiting molecules: PD-L1, ICAM-1 and CD59. To evaluate the functional impact of endothelial activation, aEC or caEC were co-cultured with peripheral blood mononuclear cells (PBMC). Alloproliferation and the relative expansion of CD4+ T lymphocyte subpopulations were assessed by flow cytometry and intracellular cytokine staining. Previously, we found that aEC are capable of expanding Th17 and FoxP3 high T regulatory cell (Treg) populations (Taflin PNAS 2011, Lion Am J Transplant 2016). The presence of intragraft Th17 correlates with shorter graft survival, whilst the proportion of Treg cells has been implicated in tolerance. aEC and caEC demonstrated a similar capacity to amplify proinflammatory subsets, Th1 and Th17. However caEC have a reduced capacity to expand anti-inflammatory FoxP3 high Treg. Quantification of IL-2, IL-6 and TGF beta in the supernatants showed no difference between aEC and caEC co-cultures. Studies using PD-L1 blocking antibodies on the endothelium identified a role for high PD-L1 expression in the suppression of Treg expansion in this allogenic model. The level of endothelial activation, induced by a pro-inflammatory environment, changes endothelial immunogenicity and notably impacts the expression of molecules involved in CD4+ T cell interactions, such as HLA antigens, PD-L1 and ICAM-1. Indeed, CD4+ T cell polarisation was differentially modulated by activated and chronically activated endothelial cells. The impaired expansion of the Treg subset in caEC cocultures results in a more pro-inflammatory profile of alloreactive CD4+ T lymphocytes, and could promote rejection and compromise allograft tolerance. AC was supported by the Société Francophone de Transplantation (SFT).